Degradation of vinyl ester resin and its composites via cleavage of ester bonds to recycle valuable chemicals and produce polyurethane. (1st January 2023) - Zhang, Ning; Cui, Xiaojing; Wang, Chizhou; Wu, Shaodi; Zhao, Yuhua; Qi, Yongqin; Hou, Xianglin; Jin, Haibo; Deng, Tiansheng
Graphical abstract: Highlights: Vinyl ester resin can be degraded in GVL-H2 O solvent with PTSA catalyst. The ester bonds of vinyl ester resins were cleaved via hydrolysis. Recycled bisphenol-A diglycidyl ether was cured into polyurethane. Amphiphilic PTSA catalyst facilitates itself entrancing into the matrix of VER. Abstract: Vinyl ester resins (VER) and its composites are widely used in chemical industry and municipal engineering. However, its dense three-dimensional network structure makes its degradation and recycling a great challenge. Herein, a novel, efficient and green degradation system gamma-valerolactone (GVL)–H2 O/p-toluene sulfonic (PTSA) was developed to degrade VER and its composites. VER was completely degraded in the GVL-H2 O/PTSA at 210 °C and 0.6 MPa. By combing SEM-EDS, IR, NMR, GPC and MALDI-TOF-MS analysis, it was clarified that VER swelled well in GVL, allowing the transfer of PTSA and H2 O through the resin matrix. The ester bonds in VER were cleaved via hydrolysis with H2 O catalyzed by the sulfonic acid of PTSA, and high value-added polymer products, i.e., copolymer of styrene and methacrylic acid (SMAA) and bisphenol-A diglycidyl ether (DGEBA), were recycled, which accounted for ca. 87.0 wt% of raw VER. DGEBA can be recycled to prepare a new PU material. The GVL-H2 O/PTSA system was also effective for degrading UPR and VER-containing composites. This work provides a practical strategy for chemical degradation and recovery of thermoset VER resins.